The retrival of structural concerns. The Towercast judgement and the return of Continental Can - Herrero Suárez, Carmen (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The CJEU has recently recognized the applicability to a concentration already carried out of the rules that penalize the abuse of a dominant position. This ruling is not an isolated phenomenon, nor is its significance limited to the field of control of business concentration, but rather, as will be the object of analysis in this paper, it constitutes one more manifestation of the change of direction that antitrust policy has been undergoing in recent years and whose scope is still being defined.